Eight new apterous Lathrobium species (Coleoptera, Staphylinidae) from Sichuan, Southwest China - Peng, Zhong (Pensoft Publishers, 2013)
Abstract. Eight apterous species of the paederine genus Lathrobium Gravenhorst, 1802 from the Chinese province Sichuan are described, illustrated, and distinguished from closely related and/or geographically close congeners: Lathrobium erlangense Peng & Li sp. n. (Erlang Shan), Lathrobium blandum Peng & Li sp. n. (Labahe N. R.), Lathrobium yelense Peng & Li sp. n. (Yele), Lathrobium obscurum Peng & Li sp. n. (Yele), Lathrobium yinziweii Peng & Li sp. n. (Yele), Lathrobium illustre Peng & Li sp. n. (Yele), Lathrobium micangense Peng & Li sp. n. (Micang Shan) and Lathrobium agglutinatum Assing & Peng sp. n. (Qingcheng Shan). The total number of described Lathrobium species from Sichuan now stands at 39, that of mainland China at 165.